COVID-19 responses and coping in young Malaysians from low-income families - Wong, Li Ping; Farid, Nik Daliana Nik; Alias, Haridah; Yusop, Sofia Md; Musa, Zuhrah; Hu, Zhijian; Lin, Yulan (Frontiers in Psychiatry, 2023)
This study aimed to shed light on how young people from low-income families were responding to the COVID-19. This cross-sectional study recruited young people aged 18–24 years from the low-income-group communities. A convenience sampling approach was used. Google Surveys was used to gather data from the survey. The questionnaire consisted of assessment of demographic characteristics, lifestyle factors, parent–youth conflict (Parental Environment Questionnaire, PEQ), resilient coping (Brief Resilient Coping Scale, BRCS), and psychological distress (Depression, Anxiety, and Stress Scale-short form, DASS -21). A total of 561 complete responses were received. Results showed low level of parent-child conflict in the overall study population, with the median PEQ of 48.0 (interquartile range [IQR] 36 to 48). Higher parent-child conflicts were found in females than males (OR=1.75, 95% CI 1.19–2.57), and in youth from households with an income below MYR2000 than those earning MYR3001–5000 (OR= 4.39, 95% CI 2.40–8.03). Low prevalence of depression (12.5%), anxiety (15.2%), and stress (6.4%) were found. Parent–child conflict remains the strongest significant predictor for higher levels of depressive (OR=10.90, 95% CI 4.31–27.57), anxiety (OR=11.92 95% CI 5.05–28.14) and stress (OR= 4.79, 95% CI 1.41–16.33) symptoms. Poor resilient coping was the second strongest predictor for depression and anxiety symptoms. In regard to lifestyle factor, a lower level of physical exercise was associated with higher depressive symptoms. By demographics, females reported more severe symptoms of depression and anxiety than males. Young people from low-income households reported greater severity in symptoms of depression, anxiety and stress than those from higher-income households. Young people who are employed also reported greater severity in anxiety symptoms than those who are unemployed. The COVID-19 pandemic continues to have an unpredictable impact on the lives of vulnerable youth in low-income families that warrants attention in future advocacy efforts.